(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze laboratory characteristics and their association with severe pneumococcal pneumonia in children aged 2 months to under 5 years at Thai Nguyen National Hospital. Methods: A cross-sectional descriptive study was conducted on 153 children aged 2 months to under 5 years diagnosed with community-acquired pneumococcal pneumonia at the Pediatric Center, Thai Nguyen National Hospital. Results: Leukocytosis was observed in 54.2% of patients, and neutrophils ≥ 70% in 7.8%. Anemia was found in 21.7% (mild 19%, moderate 2%, severe 0.7%); hematocrit < 30% accounted for 6.5%; platelet count < 150 G/L was 0.7%. Hyperglycemia occurred in 16.3%; CRP ≥ 40 mg/L in 7.2%; urea ≥ 7 mmol/L in 4.6%; and hyponatremia in 18.3%. Lobar consolidation was the most common chest X-ray finding (38.6%), while diffuse opacities accounted for 11.1%. Severe pneumonia was significantly associated with hematocrit < 30%, leukocytosis, neutrophils ≥ 70%, CRP ≥ 40 mg/L, urea ≥ 7 mmol/L, and sodium < 135 mmol/L (p < 0.05). Conclusion: Hematocrit < 30%, leukocytosis, neutrophils ≥ 70%, CRP ≥ 40 mg/L, urea ≥ 7 mmol/L, and hyponatremia were significantly associated with severe pneumococcal pneumonia in children under 5 years, supporting early risk stratification and clinical management.